Periodic Melting of Oligonucleotides by Oscillating Salt Concentrations Triggered by Microscale Water Cycles Inside Heated Rock Pores - Ianeselli, Alan (Angew Chem Int Ed Engl, 2019)
To understand the emergence of life, a better understanding of the physical chemistry of primordial non-equilibrium conditions is essential. Significant salt concentrations are required for the catalytic function of RNA. The separation of oligonucleotides into single strands is a difficult problem as the hydrolysis of RNA becomes a limiting factor at high temperatures. Salt concentrations modulate the melting of DNA or RNA, and its periodic modulation would enable melting and annealing cycles at low temperatures. In our experiments, a moderate temperature difference created a miniaturized water cycle, resulting in fluctuations in salt concentration, leading to melting of oligonucleotides at temperatures 20°C below the melting temperature. This would enable the reshuffling of duplex oligonucleotides, necessary for ligation chain replication. The findings suggest an autonomous route to overcome the strand-separation problem of non-enzymatic replication in early evolution.